The Influence of Compensation, Workload, and Work-Life Balance on Work Loyalty with Job Satisfaction as Mediator - Permana, Riyaldi Dithia; Marliana, Reny Rian (International Journal of Educational Management and Innovation, 2026)
Background. This study examines the influence of compensation, workload, and work-life balance on employees’ work loyalty, with job satisfaction as a mediating variable.Methods. Using a quantitative approach, data were collected through a 4-point Likert scale survey of employees at the Central Bureau of Statistics in West Java Province in 2025, analyzed using a two-stage Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Results. The findings reveal that workload uniquely plays both a direct and indirect role in influencing work loyalty through job satisfaction, whereas compensation and work-life balance show no significant direct effects. This research offers novelty by applying a two-stage PLS-SEM mediation analysis in the context of Indonesia’s public sector, where empirical evidence on employee loyalty determinants remains limited. Conclusion. Theoretically, this study expands the understanding of job satisfaction as a partial mediator in loyalty formation. Practically, the findings suggest that managing workload fairness can be a more effective strategy for enhancing loyalty among public employees than solely focusing on compensation or work-life initiatives.